Impact of information technology on labour productivity in Singapore industries. - Hong, Alison Yueling. (2008)
Since the late 1970s, Singapore has identified Information technology (IT) as a strategic tool to spur about new economic growth. Till date, many studies have been found describing the positive impacts of IT on Singapore’s economy. However, only a few focused on measuring the impact of IT on labour productivity across industries. This paper seeks to fill in this gap. We quantify the impact of IT on labour productivity across six major industries in Singapore, namely the (i)Manufacturing, (ii)Construction, (iii)Commerce, (iv)Transport, Storage and Communication, (v)Business and Financial as well as the category of (vi)Others industries. Using a set of specially adjusted industrial data for Singapore, we observe a positive but weak impact of IT on labour productivity in Singapore. At the aggregate level, we find that for every 1% increase in IT capital stock, there is a 0.088% corresponding increase in labour productivity. Following the order of the industries mentioned above, the impact of IT on labour productivity is: 0.228%, 0.2%, 0.199%, 0.163%, 0.167% and 0.182% respectively, for every 1% percent increase in IT capital stock. One key implication of our results is that a better strategy for IT investments is essential and should be incorporated into one of Singapore’s investment strategy.